The Influence of Digital Content, Public Figure Self-Branding, Celebrity Worship, and Audience Motivation to Increase Audience Interest in the YouTube Starpro Indonesia Social Media Account - Vinesa Ramadhita Putri; La Mani; Anita Fedora; Samiyah Amanina; M Aras (Publikasi Indonesia, 2024)
YouTube is in the 2nd position of social media that is often used in 2023 through the official We Are Social website. This is because people are starting to leave mass media to social media. Different types of video content are very popular and widely viewed, including funny videos, short films, infotainment videos and more. This study was conducted to find out the factors behind Content Digital, Public Figure Self-branding, Celebrity Worship and Audience Motivation. YouTube can now be used as a place for marketing strategies to increase brand image or purchases through Integrated Marketing Communication (IMC). Therefore, content marketing strategy involves creating content to reach the target market. Based on that customers connect with the brand to fulfil their requirements. This study was conducted on 278 participants with ages ranging between 16-25 years old. The data were collected by questionnaire. We find that the presence of sponsorship content on YouTube has an impact on attitudes towards YouTube influencers. The three elements of entertainment, information, and interference in sponsorship content on the YouTube platform play a role in shaping attitudes towards YouTube influencers. Influencers have the potential to provide concrete benefits to prospects and customers by presenting appropriate content.